The Rule ” Single Event Cannot be Generalized” A study in Usul Al-Fiqh Science - Abdulqadir, Nooraldeen Jameel (Zanco Journal of Human Sciences, 2021)
this research contains the rule (single event that cannot be generalized) which consider as one of the most important rules that the researchers depend on during their researches, also the Mufti depends on to reply any asker, and the judges to fulfill for all cases between the plaintiff and claimant, as well as needed by the jurist to conclude the rules in the light of this rule correctly, and differentiate between any other individual rule that can be generalized. It can’t be hidden that the rule of (single event that cannot be generalized) considered as a partial rule in the science of Principles of Fiqh, it includes many texts and news that linked to partial subjects labeled in the books of Hadith, Tasir and Fiqhs as mentioned by the examples of scientist in Principle of Fiqh by practical and explanatory examples as the testimony of Khuzaima alone will be placed as two testimonies. We are desperately in need to understand the texts and see which text is special to specific class or specific individual, or which text is general and comprehensive for all without any exception for anyone. And this can’t be seen except from ones who are updated with the rules of the science of Principle of Fiqh including the rule of single event and what are related to it. The problem is not-recognizing what is single event that cannot passing its place and what is general, will lead to misleading and miss selection of the rules. This research addressing the problem by explaining, defining, showing its regulations, conditions, and distinction this rule with other rules, to simplify the topic when needed to be review.